The last consolation vanished the testimony of a Sonderkommando in Auschwitz - Gradowski, Salmen 1908-1944 (The University of Chicago Press, 2022)
"The Last Consolation Vanished is a unique first-person Holocaust account. It is by Zalmen Gradowski, who was one of the Sonderkommandos (special squads) at Auschwitz, a Jew tasked with ushering prisoners into the gas chambers, removing their bodies, salvaging any valuables, and destroying all evidence of their murders. The Sonderkommandos were forcibly recruited by SS men; when they discovered how dreadful the work they were expected to do was, a number of them committed suicide or acted with the aim of being killed by the SS. In spite of their situation, some Sonderkommandos never gave up and attempted to resist in two very interlaced ways: planning an uprising and testifying. Gradowski resisted both ways, and while the rebellion he helped to lead on October 7, 1944, was completely crushed, and Gradowski was murdered in the process, his testimony lives on. Hidden in a metal bottle in the ashes near Crematorium III, Gradowski's two lyrical accounts describe the brutality of the Nazi regime, the process of the assassination of Czech Jews, and the relationship among the men forced to assist in the horrors. But his notebooks are not the detached blow-by-blow series of declarative statements we have come to expect in narratives of this kind. In the midst of daily unimaginable horrors, Gradowski aimed to write beautifully, lyrically, movingly, to create true literature where and when one would least expect to find it. Gradowski wrote in Yiddish, and until now, his full writings have only appeared in French translation. This most exceptional text, accompanied by a preface and postface by Philippe Mesnard and Arnold I. Davidson, will be of enormous value, both in Holocaust scholarship and in continuing the remembrance of the Shoah, for many years to come"--
Keywords: Gradowski, Zalmen / 1910-1944; Auschwitz (Concentration camp); Birkenau (Concentration camp); Sonderkommandos / Poland / Oświęcim / Biography; Nazi concentration camp inmates / Poland / Oświęcim / Biography; Holocaust, Jewish (1939-1945) / Personal narratives; Jews, Polish / Biography; Autobiographies; Personal narratives